2016
DOI: 10.2494/photopolymer.29.565
|View full text |Cite
|
Sign up to set email alerts
|

Control of Phase Separation of Benzothienoisoindigo-Benzodithiophene Copolymer for Organic Photovoltaics

Abstract: A new low-bandgap polymer composed of benzothienoisoindigo (BTIDG) and benzodithiophene (BDT) was designed and synthesized. By virtue of unsymmetrical BTIDG moiety, BDT-BTIDG copolymer exhibits moderate electrochemical properties in both bandgap (1.5 eV) and the highest occupied molecular orbital (HOMO, -5.4 eV). They are 0.4 eV wider and 0.5 eV deeper than those of previous symmetric thienoisoindigo (TIDG)-BDT analogue, respectively. Although the BDT-BTIDG is highly soluble in common organic solvents like chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…13,14 Diketopyrrolopyrrole (DPP) [15][16][17][18][19][20][21][22][23] and isoindigo (IDG) [24][25][26][27][28][29][30][31][32][33][34] are relatively strong electron acceptors and have been polymerized into narrow-bandgap polymers for OPV. Based on modication of IDG, Ashraf et al, 35 Pruissen et al 36 and Koizumi et al 37 have reported the synthesis of thienoisoindigo (TIDG) and its copolymers as organic eld-effect transistors (OFETs), which is followed by applications of TIDG-based near-infrared (IR)-absorbing copolymers to OPV [38][39][40][41][42] and OFET. [43][44][45][46][47] IDG and TIDG have structural similarities to DPPs with symmetric side units of benzene (Ph) or thiophene (Th), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Diketopyrrolopyrrole (DPP) [15][16][17][18][19][20][21][22][23] and isoindigo (IDG) [24][25][26][27][28][29][30][31][32][33][34] are relatively strong electron acceptors and have been polymerized into narrow-bandgap polymers for OPV. Based on modication of IDG, Ashraf et al, 35 Pruissen et al 36 and Koizumi et al 37 have reported the synthesis of thienoisoindigo (TIDG) and its copolymers as organic eld-effect transistors (OFETs), which is followed by applications of TIDG-based near-infrared (IR)-absorbing copolymers to OPV [38][39][40][41][42] and OFET. [43][44][45][46][47] IDG and TIDG have structural similarities to DPPs with symmetric side units of benzene (Ph) or thiophene (Th), respectively.…”
Section: Introductionmentioning
confidence: 99%